Pendampingan Kegiatan Organisasi Legiun Veteran di Kabupaten Banyuwangi - Miskawi Miskawi; Abdul Shomad; Wageyono Wageyono (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Legiun Veteran Republik Indonesia or LVRI is an organization that brings together veterans of the Republic of Indonesia. LVRI Banyuwangi Regency has a routine agenda of activities. One of them is the commemoration of National Veterans Day every August 10. This community service activity is carried out in the form of mentoring this commemoration activity. The series of activities include the sowing of flowers which begins with a ceremony at the hero's graveyard and a thanksgiving event. Assistance is provided to assist in organizing events, particularly in the form of event arrangements and personnel assistance. In the Thanksgiving event, the team of lecturers helped organize the event. The students were involved as conductors and MCs. This assistance is a pioneer of cooperation to provide a forum for veterans to pass on their love for the homeland.